Prognostic Predictors for Ambulation in Thai Children with Cerebral Palsy Aged 2 to 18 Years - Orawan Keeratisiroj (2018)
© The Author(s) 2015. The objectives of this study were to determine prognostic predictors for ambulation among Thai children with cerebral palsy and identify their ambulatory status. A retrospective cohort study was performed at 6 special schools or hospitals for children with physical disabilities. The prognostic predictors for ambulation were analyzed by multivariable ordinal continuation ratio logistic regression. The 533 participants aged 2 to 18 years were divided into 3 groups: 186 with independent ambulation (Gross Motor Function Classification System [GMFCS I-II]), 71 with assisted ambulation (Gross Motor Function Classification System III), and 276 with nonambulation (Gross Motor Function Classification System IV-V). The significant positive predictors for ambulation were type of cerebral palsy (spastic diplegia, spastic hemiplegia, dyskinesia, ataxia, hypotonia, and mixed type), sitting independently at age 2 years, and eating independently. These predictors were used to develop clinical scoring for predicting the future ability to walk among Thai children with cerebral palsy.